THE PANDEGLANG REGENCY GOVERNMENT’S ROLE IN THE DEVELOPMENT OF CISOLONG HOT SPRING TOURISM - Pratiwi, Eka; Akmal, Diya Ul (Jurnal Res Justitia: Jurnal Ilmu Hukum, 2024)
The aims of this study is to ascertain how the Pandeglang Regency Government manages the touristy destination of Cisolong hot springs. Cisolong hot spring is one of the tourist destination that can boost the local economy and enhance local revenue. However, the ownership of the Cisolong hot spring business license remains unclear, resulting in less-than-optimal levies collection and the presence of persons who collect fees illegally. Tourists will eventually suffer from this issue, which will also affect the destination's main draw. This study used the legal-empirical method and is bolstered by normative data analysis. The data used are primary data (Interviews and Observations) and secondary data (Legislation, Books, Journals, and relevant materials sourced from the Internet) which are then processed and narrated using words with scientific logic. The result showed that the Pandeglang Regency Government's tourism development strategy was quite good. However, the development strategy is still unable to address the issues that arise. The management and implementation of the Cisolong hot spring tourism destination must be closely monitored by the Pandeglang Regency Government. In order to attract more tourists, promotional events such as a Pandeglang culinary and cultural festival must be held. This will affect how the community's economy develops, how much money is generated locally, and how Pandeglang's cultural values are sustained